Hubungan Layanan Bimbingan Belajar Dengan Motivasi Berprestasi Peserta Didik - Sabar Lesmana (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
This study is intended to discover the correlation between study counseling service and achievement motivation. This study implemented at East Jakarta 287 Junior High Schools. The research method used was survey, which means the researcher gather information from a certain sample of a population by asking through questionnaires. To analyze the data, the researcher used product moment correlation and information gathered through questionnaires, in the form of a modified behavior scale (Likert scale.) Based on the data analyzed about the correlation between study counseling service and achievement motivation for student of eighth grade in East Jakarta 287 Junior High Schools, the values of rcount was obtained as 0,670 while rtable was 0,334. This proves that rcount were bigger than rtable (0,670 >0,334) with N value = 35 on significant level of 5%. By which, this study concludes quantitatively that there is a positive correlation between study counseling service and achievement motivation for student